Diketo acids and their amino acid/dipeptidic analogues as promising scaffolds for the development of bacterial methionine aminopeptidase inhibitors. Issue 43 (14th May 2015) - Masood, Mir Mohammad; Pillalamarri, Vijay K.; Irfan, Mohammad; Aneja, Babita; Jairajpuri, Mohamad Aman; Zafaryab, Md.; Rizvi, M. Moshahid A.; Yadava, Umesh; Addlagatta, Anthony; Abid, Mohammad
<x xml:space="preserve">Abstract</x> Diketo acids and their peptidic analogues were designed and synthesised as bacterial MetAP inhibitors. In the enzymatic assay, the representative compound 5e showed excellent inhibition of bacterial MetAPs with no cytotoxicity.